2004
DOI: 10.1148/rg.244035149
|View full text |Cite
|
Sign up to set email alerts
|

From the RSNA Refresher Courses

Abstract: Acute cholecystitis is the most common cause of acute pain in the right upper quadrant (RUQ), and urgent surgical removal of the gallbladder is the treatment of choice for uncomplicated disease. However, cross-sectional imaging is essential because more than one-third of patients with acute RUQ pain do not have acute cholecystitis. In addition, patients with complications of acute cholecystitis, such as perforation, are often best treated with supportive measures initially and elective cholecystectomy at a lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This rare condition, affecting 0.9% -3.2% of patients with biliary disease [3], is due to the close anatomic relationship between the gallbladder and the duodenum and the proximal transverse colon. As a result, chronic inflammation of the gallbladder may lead to chronic perforation and fistulous communication to these structures [4]. In a series of 10 patients Oikarinen et al [5] demonstrated that acute or chronic cholecystitis is a significant predisposing factor of internal biliary fistula and that, as it happened in the case described above, the most frequent is the cholecysto-duodenal type.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This rare condition, affecting 0.9% -3.2% of patients with biliary disease [3], is due to the close anatomic relationship between the gallbladder and the duodenum and the proximal transverse colon. As a result, chronic inflammation of the gallbladder may lead to chronic perforation and fistulous communication to these structures [4]. In a series of 10 patients Oikarinen et al [5] demonstrated that acute or chronic cholecystitis is a significant predisposing factor of internal biliary fistula and that, as it happened in the case described above, the most frequent is the cholecysto-duodenal type.…”
Section: Discussionmentioning
confidence: 96%
“…This latter may be seen if the tract is enhanced by positive oral or air contrast material. A secondary sign that may be useful is the identification of oral contrast material within the gallbladder [4] [7]. One potential drawback of CT is that 15% -25% of gallstones appear as isoattenuating relative to bile or fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the daily practice, US is still the primary imaging modality when GBS and acute cholecystitis are suspected [1,2]. In an acute setting, doubtful or difficult cases on US are evaluated additionally with CT [10].…”
Section: Discussionmentioning
confidence: 99%
“…Acute cholecystitis occurs in about one-third of patients with acute right upper quadrant (RUQ) pain, [ 1 ] which can also occur in various diseases, including chronic cholecystitis, acute pancreatitis, diverticulitis, colitis, appendicitis, Fitz-Hugh-Curtis syndrome, ureteral stone, and omental infarction. [ 2 ] In 1 study of patients with acute RUQ pain, only about one-third had acute cholecystitis (34.6%), while others had chronic cholecystitis (32.7%) or a normal gallbladder (32.7%).…”
Section: Introductionmentioning
confidence: 99%